2015
DOI: 10.1177/1535370215593826
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-3 in autoimmunity and autoimmune diseases

Abstract: Galectin-3 (gal-3) is a b-galactoside-binding lectin, which regulates cell-cell and extracellular interactions during self/ non-self-antigen recognition and cellular activation, proliferation, differentiation, migration and apoptosis. It plays a significant role in cellular and tissue pathophysiology by organizing niches that drive inflammation and immune responses. Gal-3 has some therapeutic potential in several diseases, including chronic inflammatory disorders, cancer and autoimmune diseases. Gal-3 exerts a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
92
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(106 citation statements)
references
References 131 publications
1
92
0
3
Order By: Relevance
“…growth factor receptors, integrins and members of the Notch family, and other extracellular matrix molecules [139]. In cancer, LEG3 seems to participate to the membrane dynamics of cell migration and in the escaping of the T cells-mediated immune-response [140]. On the basis of its overexpression and of its functions in the breast cancer cells, LEG3 has been recently candidated as biomarker for the triple-negative breast cancer progression [141].…”
Section: Galectin Leg3 (Lgals3)mentioning
confidence: 99%
“…growth factor receptors, integrins and members of the Notch family, and other extracellular matrix molecules [139]. In cancer, LEG3 seems to participate to the membrane dynamics of cell migration and in the escaping of the T cells-mediated immune-response [140]. On the basis of its overexpression and of its functions in the breast cancer cells, LEG3 has been recently candidated as biomarker for the triple-negative breast cancer progression [141].…”
Section: Galectin Leg3 (Lgals3)mentioning
confidence: 99%
“…In addition to its regulatory role in T-cell activation and immune tolerance, galectin-3 may be associated with tumor development as well as the destructive phenotype of tumors [29,30]. Intracellular galectin-3 supports tumor growth, metastasis, and survival [31]. However, some studies revealed that the soluble form of galectin-3 did not influence the development of tumor cells; instead, it balanced the tumor-responsive T-cell function by inducing T-cell activation and apoptosis in vitro [32].…”
Section: Galectin-3 In Immune Response and Cancer Biologymentioning
confidence: 99%
“…They are constitutively expressed by many cell lines, such as epithelial and endothelial cells from the skin, lung, or gut, as well as immune cells and fibroblasts. They are localized both extracellularly and intracellularly (in cytoplasmic or nuclear compartments) and take part in a wide range of biological processes, such as cell adhesion, cell migration, signaling, intracellular trafficking, cell proliferation, apoptosis, gene expression regulation, inflammation, and immune response . These activities have profound effects in many pathologies such as cancer, autoimmune disorders, fibrosis, arthritis, obesity, cardiovascular disease and infection .…”
Section: Introductionmentioning
confidence: 99%